049 Is the out of hours acute neurology service provision in South West London equitable?. Issue 6 (27th May 2022) - Yiu, Daniel; Harral, Josie; Fisk, Monica; Nitkunan, Arani
Abstract : Providing equitable access to neurologists out of hours regardless of whether a hospital is a neurosciences centre or a district general hospital (DGH) is key to ensuring excellent patient care for all. The aim of this audit was to determine whether there was variability in the out of hours referrals across South West London (SWL). Data were collected from June to August 2020. We found a large disparity - 78% of referrals were from the hospital aligned with the neurosciences centre although it accounted for 31% of the SWL population and 46% of acute admissions. 46% of the calls received by trainees at the neurosciences centre were discussed with the consultant, with 5% of cases requiring transfer. 84% of referrals from DGHs were advised to contact local teams for continued input. Conditions with established pathways such as seizures (23% of referrals) and headaches (11%) were less likely to require escalation to the consultant on-call. The awareness of a regional out of hours service is being addressed at the DGHs. Increasing trainee time at DGHs with the Shape of Training changes will hopefully increase trainees' awareness of DGH neurology teams. We aim to repeat this analysis next year. Acknowledgements – SWL consultants, trainees in SWL daniel.yiu93@gmail.com